2017
DOI: 10.1590/1517-869220172304173106
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise on Physical Fitness and Anthropometric Variables in Ex-Crack Cocaine Users

Abstract: Introduction: Worldwide cocaine use in all its various forms is increasing; cocaine users exceeded 17 million in the world. In Brazil, this data is also alarming. A survey conducted in 2010 found that the country has more than 900,000 crack-cocaine users. Objective: To evaluate the effects of exercise on anthropometric variables and components of physical fitness in ex-crack cocaine users. Methods: Randomized controlled trial with 20 men, divided into exercise group (n=10) and control group (n=10), admitted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Next, 101 full texts were read and 74 were excluded (see Fig 1 ), which left with 27 studies. After screening the list of references of these 27 studies, 16 new articles were identified for a total of 43 [ 29 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…Next, 101 full texts were read and 74 were excluded (see Fig 1 ), which left with 27 studies. After screening the list of references of these 27 studies, 16 new articles were identified for a total of 43 [ 29 71 ].…”
Section: Resultsmentioning
confidence: 99%